Fragile states: Analytically vacuous, politically useful - Maria-Louise Clausen; Peter Albrecht (Danish Institute for International Studies (DIIS), 2022)
Why is it still relevant to probe the notion of fragility when the concept has been so heavily criticised? Because it continues to be used in policy on conflict, security and development. For example, the United Nations names fragility as a major challenge to achieving the Millennium Development Goals and a threat to global security. This working paper explores how the concept of fragility has evolved and been adapted since the inception of the failed state concept in the 1990s to the current focus on fragile situations. The paper then argues that this reflects the vacuous character of the concept, which makes it politically flexible rather than a precise diagnostic tool. It provides justifications for interventions that are often prioritised due to the impact of fragile states on 'our' (Western) security. We trace how this evolving understanding of fragility has been utilised in two cases, Somalia and Iraq, through the prism of security-related programming, often referred to as Security Sector Reform. We illustrate how the concept is applied to very diverse cases in ways that tend to prioritise the interests of the interveners over those of the people who are purportedly intervened on behalf of.
Keywords: 330; Defence and security policy; Terror Development policy; World politics; The politics of great and emerging powers; Diplomacy and international organisations